1979
DOI: 10.1111/j.1432-1033.1979.tb13212.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Protein Factor that Reverses the Inhibition of Protein Synthesis by the Heme‐Regulated Translational Inhibitor in Rabbit Reticulocyte Lysates

Abstract: We have purified and partially characterized a supernatant factor which reverses the effect of the heme‐regulated translational inhibitor on protein synthesis in rabbit reticulocyte lysates. The anti‐inhibitor restores protein synthesis activity in heme‐deficient lysates (and in lysates to which the inhibitor has been added) to the level observed in the presence of heme. The factor has no effect on the phosphorylation of eIF‐2 by the inhibitor nor on any reaction carried out with purified initiation factors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 41 publications
0
53
0
Order By: Relevance
“…For example, in the original work describing the identification of seven initiation factors required for globin mRNA-directed translation initiation (10, 11), eIF4F was not identified as a separate translation initiation factor because the protein was present as a contaminant in purified preparations of eIF3 and eIF4B (45). Likewise, eIF2B forms a stable complex with eIF2 and can be isolated as a stable eIF2⅐eIF2B complex from cell extracts (46,47). These two proteins which have distinct functions in translation initiation can only be separated from each other by high salt glycerol gradient centrifugation (47).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the original work describing the identification of seven initiation factors required for globin mRNA-directed translation initiation (10, 11), eIF4F was not identified as a separate translation initiation factor because the protein was present as a contaminant in purified preparations of eIF3 and eIF4B (45). Likewise, eIF2B forms a stable complex with eIF2 and can be isolated as a stable eIF2⅐eIF2B complex from cell extracts (46,47). These two proteins which have distinct functions in translation initiation can only be separated from each other by high salt glycerol gradient centrifugation (47).…”
Section: Resultsmentioning
confidence: 99%
“…The exchange of GTP for GDP in the eIF-2 * GDP complex is catalyzed by a multimeric protein factor called eIF-2B (previously called reversing factor or GEF) (1,22,26,33,41). The guanine nucleotide exchange is a prerequisite for eIF-2 to enter another initiation cycle and bind the initiator tRNA, MettRNAi.…”
mentioning
confidence: 99%
“…However, recently we have found that eIF-2 occurs as a complex with a protein, designated anti-HRI [99]. This complex is 5-6-fold more efficient during methionyl-puromycin formation than eIF-2 alone, resulting in the recycling of eIF-2.…”
Section: Eif4dmentioning
confidence: 99%
“…Since this discovery attempts were made to show that phosphorylated eIF-2 was inactive in initiation of protein synthesis, but no concluding evidence was obtained [24,98]. Phosphorylation of eIF-2 seemed to have neither an effect on its activity in model assay systems [24, 98,99], nor on its capacity to recycle [loo]. It was concluded that the phosphorylation of eIF-2 is not the sole cause of cessation of protein synthesis.…”
Section: Eif4dmentioning
confidence: 99%